Práticas de subjetivação e construções identitárias em Cora Coralina - Lima, Sueli Gomes de (2008)
Theoretically based on the principles of French Discourse Analysis formulated by Michel Pêcheux , our study presents some reflections about the subjectivity practices and the identity constructions in Cora Coralina s work. For that purpose, we chose a literary corpus which is composed by poems from three of Coralina s books: Meu livro de cordel, Poemas dos becos de Goiás e estórias mais and Vintém de cobre meias confissões de Aninha. Assuming the principle that the subject (or subjects?) in the mentioned literary corpus is built by historical, ideological and social elements, our study in a discoursive orientation intends to explicit the constitution of the subject by analyzing the elements of the sociohistorical reality. Therefore, our focus is the discoursive subject that is manifested in the discourse, considering that, in the Discourse Analysis domain, the empirical author category is erased: the author disappears and the discoursive subject emerges, built as an enunciator of different subject-positions, of other discoursive subjects. The notion of subject becomes then the guiding concept for this research, which is based both on Michel Pêcheux s subject-form concept and on Michel Foucault s subject-position theory. We intend to present some reflections about subjectivity, singularity and identity in order to better understand the discoursive subject, which nature refers to its own constitutive exteriority. We also intend to underline the pertinence of the articulation of these concepts to the identity practices, which are built by the discourses themselves. For that, we used both the notion of subjectivity, according to Michel Foucault s theoretical postulates, and the notion of identity by scholars such as Tomaz Tadeu Silva, Kathryn Woodward and Stuart Hall. By considering that the conditions of production of the discourses are historical, political and mainly contradictory, we mean to analyze how social relations permit the configuration of the discoursive identity characterized by plurality. We also present the enunciative heterogeneities as a theoretical fundament according to what is postulated by Jacqueline Authier-Revuz , which are explored in order to show the dispersion of the discoursive subjects and the notion of discoursive formation in the perspective of two theorists: Michel Pêcheux and Michel Foucault. Finally, considering the decentralization of the subject, we intend to analyze the subjectivity movement and also to identify the assumed subject-positions, according to the discoursive and ideological formations in the sociohistorical imaginary of the discoursive sequences. It is our purpose, as well, to show the subjectivity processes and the identity constructions of the discoursive subjects in Cora Coralina s work.